2011
DOI: 10.4061/2011/359242
|View full text |Cite
|
Sign up to set email alerts
|

Osteoimmunopathology in HIV/AIDS: A Translational Evidence-Based Perspective

Abstract: Infection with the human immunodeficiency virus-1 (HIV) and the resulting acquired immune deficiency syndrome (AIDS) alter not only cellular immune regulation but also the bone metabolism. Since cellular immunity and bone metabolism are intimately intertwined in the osteoimmune network, it is to be expected that bone metabolism is also affected in patients with HIV/AIDS. The concerted evidence points convincingly toward impaired activity of osteoblasts and increased activity of osteoclasts in patients with HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 93 publications
2
13
0
Order By: Relevance
“…Our data showed that osteocalcin as a bone formation biomarker is lower than desirable concentration in these patients and had positive correlation with vitamin D serum level. This finding is in agreement with the previous studies [14,26]. …”
Section: Discussionsupporting
confidence: 94%
“…Our data showed that osteocalcin as a bone formation biomarker is lower than desirable concentration in these patients and had positive correlation with vitamin D serum level. This finding is in agreement with the previous studies [14,26]. …”
Section: Discussionsupporting
confidence: 94%
“…This higher scale network could be represented as an interconnection of texts via hyper-text links. A health information-Wayback structure, that is directly connected to, and is an integral part of the Wayback database, could be constructed, which would for instance comprise the topic osteoimmunopathology in HIV & AIDS [9]. This novel perspective on HIT structure, which ought to be articulated in view of future improvement in the technology, such as the Semantic web meta-data edifice, would represent an ensemble of universes of data and information that could be collected, connected, and linked - from the basic fundamental osteoimmune data describing the intertwined cross-talk between cellular immunity and bone metabolism during development and aging in health, and in HIV disease & AIDS related pathologies, to the genomic and proteomic signatures of specific osteo-immunopathologies, and could include subjects from rheumatoid arthritis to temporomandibular joint disorders, to the best available evidence for diagnosis and prognosis, critical summaries and lay-language summaries, and conceptual and textual data mining as outlined above - with patient histories, values and preferences (inter-linked at this point with other databases) in order to ensure the best available patient-centered health bioinformation technology-based clinical decisionmaking database of databases.…”
Section: Figurementioning
confidence: 99%
“…Ramirez-Amador et al (2009) [1.3.2.] Elevated rates of liver (Price and Thio, 2010) and kidney (Islam et al, 2012) diseases, hypertension (Peck et al, 2014), diabetes (Zhang et al, 2014), and disturbed bone homeostasis (Arora et al, 2010;Barkhordarian et al, 2011;Ofotokun and Weitzmann, 2011) in HIV+ adults are well documented. These systemic diseases are influenced by HIV and ART; however, persons with HIV infection may also have high levels of traditional risk factors (Volberding and Deeks, 2010) such as (older) age, male gender, smoking, genetic predisposition/family history, being overweight, dietary contributions, and a lack of physical activity (US Department of Health and Human Services (USDHHS), 2015b); thus, these potential confounding variables should be examined to avoid spurious associations between these conditions and ART.…”
Section: Oral Diseasesmentioning
confidence: 99%
“…HIV‐associated immunopathology has been related to reduced bone mineral density (BMD) (Arora et al , ; Gutierrez and Masia, ), resulting in an increasing risk for osteoporosis (Brown and Qaqish, ) and bone fracture in HIV‐infected individuals (Triant et al , ). For example, both HIV and ART may disturb the osteoclast‐osteoblast equilibrium that, in sum, favors the destructive forces of osteoclast activity (Barkhordarian et al , ; Ofotokun and Weitzmann, ). A recent, singular report found that mandibular BMD in menopausal HIV+ women may be reduced in comparison to older HIV‐negative women (Caputo et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation